BRG1 Stimulates Endothelial Derived Alarmin MRP8 to Promote Macrophage Infiltration in an Animal Model of Cardiac Hypertrophy - Li, Zilong; Zhang, Yuanyuan; Zhang, Yangxi; Yu, Liming; Xiao, Bin; Li, Tianfa; Kong, Xiaocen; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Endothelial cell derived angiocrine factors contribute to the disruption of homeostasis and the pathogenesis of cardiovascular diseases in response to stress stimuli. In the present study we investigated the role of BRG1, a key component of the chromatin remodeling complex, in the regulation of angiocrine signaling. We report that angiotensin II (Ang II) induced pathological cardiac hypertrophy was attenuated in mice with endothelial-specific ablation of BRG1 (ecKO) compared to the control mice (WT). Mitigation of cardiac hypertrophy as a result of BRG1 deficiency was accompanied by decreased macrophage homing to the hearts. This could be explained by the observation that the ecKO mice exhibited down-regulation of myeloid-related protein 8 (MRP8), a well-established chemokine for macrophages, in vascular endothelial cells compared to the WT mice. Further analysis revealed that BRG1 mediated the activation of MRP8 expression by Ang II treatment in endothelial cells to promote macrophage migration. BRG1 was recruited to the MRP8 promoter by interacting with hypoxia-inducible factor 1 (HIF-1a). Reciprocally, BRG1 facilitated the binding of HIF-1a to the MRP8 promoter by sequentially recruiting histone acetyltransferase p300 and histone demethylase KDM3A. Depletion of either p300 or KDM3A repressed the induction of MRP8 expression by Ang II and ameliorated macrophage migration. In conclusion, our data delineate a novel epigenetic whereby Ang II stimulates MRP8 production and macrophage homing to promote cardiac hypertrophy.